"Man ska inte dö med plus på flexen" - Wihl,Sofia; Svensson,Elwira (2025)
This study aimed to examine how social workers at child and family units within the Swedish municipal social services experience and manage their workload, as well as describe the opportunities to influence their work situation. The theoretical framework used was Hirschman’s theory of exit, voice, and loyalty and Karasek and Theorell’s demand-control-support model, supplemented with the concepts of exit spirals and ethical stress. The study used a qualitative approach with seven semi-structured interviews with social workers doing child and family assessments or being responsible for children in care. The results showed that the social worker’s workload varied over time, but was often high and not considered reasonable for their employment. The high workload was caused by heavy demands, low control, lack of organisational support, and the emotional dimensions of social work practice, and was primarily managed by individual or collegial strategies. The opportunity to discuss the unmanageable workload at the workplace was described as being used to a great extent. As a result of stable collegial relations and an often supportive manager, the scope for discussion was open and inclusive. Although the work environment encouraged the strategy of voice, there was a lack of significant influence and changes. This either led to acceptance of the workload or intentions to exit. To avoid placing the responsibility for the work situation on an individual or collegial level, the employer must take action and provide emotional and practical support. If not, there is a risk of the unmanageable workload becoming a normalized part of the role of a social worker.
Keywords: social worker; workload; stress; support; voice; exit